Exchange Rate Fluctuations and International Portfolio Rebalancing in Thailand - Gyntelberg, Jacob (IMF Working Papers; Working Paper ;, 2012)
We present empirical evidence that the Thai baht's value is driven in part by investors' cross-border equity portfolio rebalancing decisions. Our results are based on comprehensive datasets of FX and stock market transactions undertaken by nonresident investors in Thailand in 2005 and 2006. Higher returns in the stock market relative to a reference stock market are associated with net sales of equities by these investors and a depreciation of the Thai baht. Net purchases of Thai equities lead to an appreciation of the Thai baht. Foreign investors do not appear to hedge the foreign exchange risk related to their stock market positions.